2019
DOI: 10.5005/jp-journals-10054-0077
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Therapeutic Efficacy of Antioxidants in Psoriatic Cases

Abstract: Introduction: Psoriasis is one of the debilitating diseases of the skin of chronic inflammatory origin. Oxidative stress is considered as the culprit for the oxidant and antioxidant imbalance, resulting in psoriasis. Objectives: This study was undertaken to know the effects of oxidative stress in the origin and development of psoriasis and to evaluate the beneficial effect of antioxidant therapy in psoriatic patients along with conventional treatment. Materials and methods: Thirty-three patients of age group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Madhulatha and Vijayabhaskar (2019) 15 reported antioxidant supplementation therapy along with conventional therapy for 8 weeks, in psoriatic patients, resulted in a significant decrease in mean serum levels of MDA, while the total antioxidant levels increased significantly. Relhan et al,2002 16 in their study observed the same results.…”
Section: Discussionmentioning
confidence: 99%
“…Madhulatha and Vijayabhaskar (2019) 15 reported antioxidant supplementation therapy along with conventional therapy for 8 weeks, in psoriatic patients, resulted in a significant decrease in mean serum levels of MDA, while the total antioxidant levels increased significantly. Relhan et al,2002 16 in their study observed the same results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on psoriasis patients corroborated the effectiveness of exogenous antioxidants as a supplementary therapy in the course of pharmacological psoriasis treatment. Madhulatha and Vijayabhaskar [ 157 ] demonstrated a significant decrease of MDA and increased total antioxidative capacity (TAC) in the blood serum of patients receiving pharmacological treatment already after eight weeks of therapy using a mixture of antioxidants (30 mg β-carotene + 27.5 mg zinc sulphate monohydrate + 0.2 mg monohydrated selenium dioxide + 2 mg manganese + 1 mg copper). In a study by Kharaeva at al.…”
Section: Clinical Studiesmentioning
confidence: 99%